Role of Artificial Intelligence in the Risk Management at Construction Field: A Bibliometric Review - Septiani, Anggita Puspita; Budi, Savitri Citra; Prihaswan, Irawadi (Jurnal Kesehatan Vokasional, 2025)
Background: The construction industry had high risks that required effective risk management to ensure safety and business sustainability. Artificial intelligence (AI) had the potential to improve analysis and decision-making in risk management. However, the trend of AI implementation in this field had not been extensively studied through bibliometric analysis.Objective: This study identified trends in scientific literature regarding the role of AI in risk management in the construction sector.Methods: This study used a quantitative bibliometric approach. Data from 76 articles in the Scopus database for the period 2014–2024 were analyzed statistically, and keyword co-occurrence was mapped using VOSviewer.Results: Publications showed a significant increase since 2015, especially after 2018. This reflected the increasing adoption of AI in risk analysis and incident prevention. Data analysis confirmed that AI proved helpful in managing risks in construction and project management.Conclusion: AI played a crucial role in improving construction risk management and was developing rapidly. This technology had great potential to reduce accidents and support sustainable practices. These findings provided insights for researchers and practitioners to optimize the utilization of AI in the construction industry.